"Hey Students, How Was That First Semester of Remote Instruction?": Graduate Students' Reflections on Remote Learning During COVID-19. Issue 2 (3rd April 2021) - Damast, Deborah; Cohen, Patricia; Martinez, Deanna Lynn
Abstract: How have entering graduate students adapted to remote learning in dance education during COVID-19? How can faculty and administrators support our students in their remote education? Students responded via e-mail or anonymous Google Form to four questions that addressed ways in which they were engaged and challenged by remote learning, their strategies for success, and advice to others. The limited relevant literature echoes our students' reflections that remote learning is an individualized experience, in which learning is dependent on their resources, access (geographic, time, or otherwise), family life, communication styles, affinity or aversion to technology, learning styles, and supplemental experiences off screen. We conclude that a strategic approach to wellness and self-care, communication, and organization will benefit future students' learning regardless of the ways in which they perceive remote learning.